PENURUNAN INTEGRASI KAIDAH BOOLE DAN APLIKASINYA UNTUK MENYELESAJKAN INTEGRAL TENTU MENGGUNAKAN PROGRAM PASCAL - Afgani, Muhammad Win (Universitas Islam Negeri Raden Fatah, 2012)
The aim of this paper is to derivate Boole rule integmtion using the 4th order of Newton-Gregory Polynomial and Richardson earapolation. The form formula is applied in pascal programming to find the solution of definite integeral toward continue function and function that is tabulated.